ANALISIS PROBLEMATIKA INDISIPLINER SISWA SMP PLUS HIDAYATUL MUBTADIIN KEMBANG PURWOASRI SINGOSARI MALANG - Bahroin Budiya; Nor Mubin (Attaqwa: Jurnal Ilmu Pendidikan Islam, 2023)
The purpose of this research is to find out the disciplinary actions of students. Because today's disciplinary problems are mushrooming from young people to adults. There are so many of them who take action without thinking about the consequences of what they have done. This research was conducted at SMP Plus Hidayatul Mubtadiin Kembang Purwoasri Singosari, which is where the author conducted the research. Based on the observations made, disciplinary actions are very common here. Problems that are obtained by the majority of students from their peers. It is at this age that many junior high school students try things they haven't done before or in other words they are very curious about new things. The results of this study were that the researcher found two factors, namely internal factors, namely laziness, not yet doing assignments, late for class and so on (2) external factors, namely waiting for friends to leave together to be the cause of being late for school, teachers who were too fast in writing on the blackboard so that students are left behind in subject matter which causes students not to record subject matter completely, and noise in class which disturbs other students. With the condition of problematic students, the teacher must also carry out repressive social activities so that mistakes made by students are not continuously made and sustainable.